2317. Multicenter Retrospective Cohort Study of Pediatric Osteomyelitis. (26th November 2018) - Treinen, Charles; Otto, William; Simonsen, Kari; Saux, Nicole Le; Bowes, Jennifer; Green, Julianne; Jackson, Mary Anne; Woods, Charles; Snowden, Jessica; Lyden, Elizabeth; Davies, H Dele
Abstract: Background: There is controversy about the appropriate management of acute osteomyelitis in children. Methods: Retrospective cohort study of presentation, management and outcomes of all patients admitted with acute osteomyelitis (<2 weeks duration) during 2010–2016 at 4 US and Canadian tertiary care hospitals (hosp). Long-term complications (LTC) were defined as amputation, limp, chronic or secondary infection, or readmission. Overall complications included LTC, admission to ICU and delayed surgery (>72 hours). Results: 712 patients were admitted, with a median age of 8.0 years. There were significant differences in rates of initial use of MRI for diagnosis, MRSA, PICC insertion, hosp stay and IV antibiotic duration (Table 1). Clindamycin (45.7%), cefazolin (24.1%) and vancomycin (13.7%) were the most common IV antibiotics used while clindamycin (47.1%) and cephalexin (38.6%) predominated for oral. The median age of patients with MRSA was similar to those without MRSA (8.2 vs. 7.8 years, P = 0.18), but MSSA patients were older (9.6 vs. 6.9 years, P < 0.0001). Contiguous septic arthritis was more common in younger children (6.8 vs. 8.5 years, P < 0.001). MRSA patients had higher overall complication rates (25.2% vs. 10.0%, P < 0.0001), but long-term complications were unrelated to duration of IV or total antibiotics. Conclusion: Despite significant variation in management, long-term complication rates were similar across US and Canadian sites with different MRSA rates. These data support equivalence of shorter (≤ 4 days) duration of IV antibiotics and reduced need for PICC insertion for pediatric osteomyelitis. Disclosures: All authors: No reported disclosures.